PERANAN LINGKUNGAN BAHASA DALAM PEMEROLEHAN BAHASA KEDUA - Purba, Andiopenta (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
Language is a certain place and circumstance where a language expanded used by the speech community. It consists of everything that can be heard and seen, then, it influences the process of language communication. Language environment can be divided into two categories: formal setting, which is formed by planning, and informal setting, which is formed naturally. Formal setting has important role in second language acquisition process, especially in the sequence of second language acquisition, and the succes acceleration of second language acquisition. Furthermore, informal setting has important role in second language acquisition process, especially in the learner’s peer environment, parents, family, and foreign speaker environment.Key words: second language acquisition, language environment